PENERAPAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA UNTUK TANAMAN HIDROPONIK - Dhian Herdhiansyah; Asriani Asriani; La Ode Midi (Universitas Mataram, 2023)
The rise of growing plants by the hydroponic method is currently popular because it does not require large areas of land and land. Hydroponic planting using the NFT (Nutrient Film Technique) method requires airflow to be maintained; its function is to distribute nutrient water to plant roots. In practice, PLN is used to turn on the water pump, but if the energy supply from PLN dies due to interference or negligence, the supply of plant nutrients will also stop, so a solution is needed. The purpose of community service activities (PKM) aims to increase knowledge and skills in applying a solar power generation system for hydroponic plants, especially for activity partners, namely the Nuri Holti Hidro Business. The activity was held on 29 - 30 June 2022 and attended by 20 participants. PKM stages: (1) the preparation stage - team meeting, coordination with partners, and preparation of facilities and equipment; and (2) the implementation stage of training and technical guidance. The training was carried out using the demonstration method. The pre-test evaluation results revealed that the training participants' knowledge and skills regarding applying solar power generation systems for hydroponic plants was only 40 per cent. Meanwhile, the results of the post-test evaluation after the training activities for implementing solar power generation systems for hydroponic plants. There was an increase of 85 per cent in the training participants. Applying a solar power generation system for hydroponic plants is more flexible for hydroponic plant locations that are open / in the sun.